(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Teaching English has become an integral part of the modern education system. It is known that the use of various technologies and the effective use of methods make language teaching easier. This article discusses the effectiveness of using information and communication technologies in learning English and makes some suggestions.